A Europol e as novas ameaças à segurança interna da União Europeia - Gonçalves, Paulo Miguel Santos (2018)
The old forms of transnational organized crime and terrorism have reinvented their paradigm of action through the introduction of new actors and modus operandi. Terrorism and transnational organized crime are clearly interlinked areas which constitute transnational threats, which, because of their multifaceted and international dimension, require an effective and coordinated response at EU level. This paper addresses the role of Europol in combating the new threats in the light of Regulation (EU) 2016/794 of 11 May establishing the European Police Agency - Europol. For this purpose, the new threats are characterized, the evolution of the internal security policy in operational cooperation is analyzed, the internal security architecture of the Union is dissected, as well as the functioning of Europol aimed at demonstrating their capabilities - and their legitimacy - in combating terrorism and transnational organized crime. The operations carried out by Europol between 2009 and 2015, wich are available in open source, were further assessed, whereby characterizing the type of intervention and activities undertaken. Moreover, the above-mentioned Regulation has increased the scope of action and influence of Europol at all decision-making levels, namely political, strategic, operational and tactical. This reinforcement has created a supranational European Security Agency with effective decision-making and enforcement powers. It is thus concluded that Europol contributes significantly to tackle new threats to the internal security within the European Union. Currently, Europol not only supports and reinforces the action of the Member States competent authorities, but also integrates and complements them by developing three major activities: Intelligence; Criminal Prevention; and Criminal Investigation.